2014
DOI: 10.1002/aur.1432
|View full text |Cite
|
Sign up to set email alerts
|

Prosody Recognition in Adults With High‐Functioning Autism Spectrum Disorders: From Psychoacoustics to Cognition

Abstract: Prosody is an important tool of human communication, carrying both affective and pragmatic messages in speech. Prosody recognition relies on processing of acoustic cues, such as the fundamental frequency of the voice signal, and their interpretation according to acquired socioemotional scripts. Individuals with autism spectrum disorders (ASD) show deficiencies in affective prosody recognition. These deficiencies have been mostly associated with general difficulties in emotion recognition. The current study exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 61 publications
8
59
2
Order By: Relevance
“…Previous work has found that cognitive remediation therapy (CRT, Tchanturia et al, 2014) and emotion skills training (CREST, was helpful for ED patients, which could be extended to individuals at risk for both autistic traits and eating pathology. Finally, as difficulties regulating emotions are associated with the development of a range of psychopathologies including EDs and ASD (Globerson et al, 2015), interventions targeting emotion regulation may provide a transdiagnostic approach to resilience and mental health promotion programs, and the prevention of psychopathology more broadly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has found that cognitive remediation therapy (CRT, Tchanturia et al, 2014) and emotion skills training (CREST, was helpful for ED patients, which could be extended to individuals at risk for both autistic traits and eating pathology. Finally, as difficulties regulating emotions are associated with the development of a range of psychopathologies including EDs and ASD (Globerson et al, 2015), interventions targeting emotion regulation may provide a transdiagnostic approach to resilience and mental health promotion programs, and the prevention of psychopathology more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…Emotion dysregulation and negative attitudes towards emotional expression have been found to be entwined with both EDs (Harrison et al, 2010;Svaldi et al, 2012) and ASD (Samson et al, 2013). While research has consistently found a relationship between greater emotion regulation difficulties, including restricted access to emotion regulation strategies and lack of emotional clarity in both EDs (Meyer et al, 2010) and ASD (Globerson et al, 2015), research on negative attitudes towards emotions is more limited. The few studies assessing negative attitudes towards emotions revealed significant positive associations between eating pathology and the reduced tendency to express emotions (Haslam et al, 2012), as well as the belief that expressing emotions is a sign of weakness (Meyer et al, 2010).…”
Section: Emotions As Potential Mechanisms Linking Autistic Traits Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to prosodic expressive abilities, fewer investigations have explored the processing skills of receptive prosody in individuals with ASD (McCann & Peppé, 2003;O'Connor, 2012;Globerson, Amir, Kishon-Rabin & Golan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies in this area have focused primarily on the perception of pragmatic/affective prosody (Chevallier, Noveck, Happé, & Wilson, 2011;Globerson et al, 2014;Golan, Baron-Cohen, & Hill, 2006;Golan, Baron-Cohen, Hill, & Rutherford, 2007;Grossman, Bemis, Plesa Skwerer, & Tager-Flusberg, 2010;Heikkinen et al, 2010;Järvinen-Pasley, Wallace, Ramus, Happé, & Heaton, 2008b;Jones et al, 2011;Kleinman, Marciano, & Ault, 2001;Lindner & Rosén, 2006;Peppé, McCann, Gibbon, O'Hare & Rutherford, 2007;Rutherford, Baron-Cohen, & Wheelwright, 2002). Several of these studies using complex vocal expressions (i.e.…”
Section: Introductionmentioning
confidence: 99%